Carbon with Surface‐Enriched Nitrogen and Sulfur Supported Au Catalysts for Acetylene Hydrochlorination. Issue 3 (29th January 2019) - Wang, Bolin; Zhao, Jia; Yue, Yuxue; Sheng, Gangfeng; Lai, Huixia; Rui, Jiayao; He, Haihua; Hu, Zhongting; Feng, Feng; Zhang, Qunfeng; Guo, Lingling; Li, Xiaonian
Abstract: The front cover artwork for Issue 03/2019 is provided by researchers from Industrial Catalysis Institute, Laboratory Breeding Base of Green Chemistry‐Synthesis Technology, Zhejiang University of Technology (P. R. China). The image shows carbon with surface‐enriched nitrogen and sulfur supported Au catalysts for acetylene hydrochlorination. The sulfur species on the carbon surface was considered to be able to selective formation of pyrrolic nitrogen against pyridinic nitrogen, which significantly influence the catalytic performance of Au‐based catalysts.. See the Full Paper itself at https://doi.org/10.1002/cctc.201801555 . Abstract : "An innovative strategy that tunes the nitrogen speciation" This and more about the story behind the research featured on the front cover can be found in this issue's Cover Profile. Read the full text of the corresponding research at https://doi.org/10.1002/cctc.201801555 .